Analisis Konten Film Dirty Vote di Tiktok dalam Mempengaruhi Persepsi Masyarakat - Tamara Nur Fauziyah; Diryo Suparto; Didi Permadi (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to analyze how the content of the Dirty Vote film circulating on TikTok Social Media influences public perception of the election process and the results of the 2024 Election. The film "Dirty Vote" is a 1 hour 57 minute political film depicting allegations of fraud in the presidential election process in a fictional country. The research method used in this article is a qualitative approach by conducting content analysis of comments and responses from the public on TikTok social media related to the film "Dirty Vote". The results of the study show that this film succeeded in creating significant buzz and discussion on the platform. Many TikTok users expressed their opinions on the issue of fraud in the 2024 Presidential Election and shared the film with their followers. This shows that TikTok social media can be an effective tool for disseminating political information and influencing public opinion. In conclusion, the film "Dirty Vote" on TikTok social media has a significant influence on public perceptions to the issue of fraud in the 2024 Presidential Election.